PEMBANGUNAN BERBASIS GENDER - Pauzia, Restu (Musawa: Journal for Gender Studies, 2021)
Humans are social beings who live in groups and form an order of social life such as building a country. One of the ways that the government takes to realize the welfare of its people is through development. With development, the right to welfare for the whole community can be achieved. The concept of welfare in development is not seen as the same thing. Every society in this world has a different level of wealth. This is because they do not only take into account gender differences, but also all vulnerable groups. Basically, development is held for improvement. This means the desire to grow based on individual or group strengths depends on the situation and condition of human labor and social structure. When viewed from the development process to date, there are still many disadvantages for vulnerable groups who also participate in economic growth in the community. Gender perspective is very important in determining policies that will be implemented for the development to the process and results, especially laws which do not regulate detrimental losses to vulnerable groups. This shows that women and other vulnerable groups should receive special attention in the development because they are at a higher risk of physical and non-physical violence.